Parental Vaccine Hesitancy in Quebec (Canada) - Dubé, Eve (PLoS Curr, 2016)
Introduction: "Vaccine hesitancy" is a concept frequently used in the discourse around vaccine acceptance. This study aims to contribute to the ongoing reflections on tools and indicators of vaccine hesitancy by providing results of a knowledge, attitudes and beliefs (KAB) survey conducted among parents. Methods: Data were collected in 2014 through a computer-assisted telephone interview survey administered to a sample of parents of children aged between 2 months and 17 years of age. Results: The majority of the 589 parents included in the analyses agreed on the importance of vaccination to protect their children’s health and to prevent the spread of diseases in the community. The majority of the parents (81%) reported that their child had received all doses of recommended vaccines and 40% of parents indicated having hesitated to have their child vaccinated. Fear of adverse events and low perceived vulnerability of the child or severity of the disease were the most frequent reasons mentioned by these vaccine-hesitant parents. In multivariate analyses, KAB items remaining significantly associated both with an incomplete vaccination status of the child and parents’ vaccine hesitancy were: not thinking that it is important to have the child vaccinated to prevent the spreading of diseases in the community; not trusting the received vaccination information and having felt pressure to have the child vaccinated. Discussion: Further researches will be needed to better understand when, how and why these beliefs are formed in order to prevent the onset of vaccine hesitancy.